FLORA FÓSIL DE ESTAIDSPORAS CRISÓFICEAS (CHRYSOPHYTA) EN SEDIMENTOS RECIENTES DEL LAGO NAHUEL-HUAPI (RIO NEGRO, ARGENTINA) (Ameghiniana, 2014)
This paper deals with the description of a fossil chrysophycean cysts flora from recent sediments of Brazo Campanario, a branch of Lake Nahuel-Huapi (Río Negro, Argentina). The descriptions of the morphotypes are based on S.E.M. observations in al! cases and on L.M. ones in many of them. The fifteen fossils cysts here described were the most frequently found in the coreo Six ofthem are new morphotypes for science and all are new records for Argentina.